Cisco Certified Design Expert : CCDE 400-007 official cert guide - Zsiga, Zig (Cisco Press, 2023)
Trust the best-selling Official Cert Guide series from Cisco Press to help you learn, prepare, and practice for exam success. They are built with the objective of providing assessment, review, and practice to help ensure you are fully prepared for your certification exam. Cisco Certified Design Expert (CCDE 400-007) Official Cert Guide presents you with an organized test preparation routine using proven series elements and techniques. "Do I Know This Already?" quizzes open each chapter and allow you to decide how much time you need to spend on each section. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly.